Efektivitas Kebijakan Penertiban Pengemis Di Kota Malang - Nanda Erlambang (FISIP UWP, 2023)
Poverty is a concrete problem in society which is generally and systemically caused by the lack of availability of jobs, low levels of education, and individuals who do not have the competence and skills to earn money. Social phenomenon is the emergence of beggars so that they become a public problem as happened in Malang City. According to data from the Central Bureau of Statistics for the City of Malang in the period 2016 to 2018, there were 378 beggars spread throughout the city of Malang. The implementation of the beggar control policy was carried out by the Malang City government through the Malang City Regional Regulation Number 9 of 2013 concerning Handling Street Children, the Homeless, and Beggars. Qualitative descriptive methods in this study were used to understand and describe the background along with problem-solving efforts, obstacles, and supporting factors for controlling beggars in the city of Malang. So the results of this study indicate that the existence of beggars in the city of Malang is caused by the application and content of the Malang City regulations regarding control of beggars whose character is persuasive and does not cause a deterrent effect. Then the supporting factors are that the Malang City government has succeeded in implementing regional regulations and innovation program policies because of the synergy between agencies, namely the Malang City Social Service, the Malang City Civil Service Police Unit, the Mutiara Insani Social Welfare Institute and the Ministry of Social Affairs of the Republic of Indonesia.